Embodied Emotions. Le mappe corporee delle emozioni - Svorova, Dana (Aesthetica Preprint, 2021)
In the current interdisciplinary debate focused on the complexity of the human being, we witness a turning point. Body and mind, which were traditionally considered to be separated, are nowadays re-united thanks to the empiric data obtained in the cognitive neurosciences. Different scholars in this field of study, such as Damasio, Varela, Gallese and others, have addressed the specific concept of ‘embodiment’. This new concept of the mind and body, called “embodied cognition”, manifests the full extension of the cognitive dimension to include the mind, body, emotions and environment in a dynamic process characterized by their reciprocal interaction. In the meantime, one important question concerns emotions specifically. Results of scientific experimental researches in different fields of study, conducted by e.g. Pert, Coulson, Nummenmaa, emphasize the fact that the body and mind are united, thus opening the possibility to talk about ‘embodied emotions’. These studies can contribute greatly to somaesthetics and emphasize a positive approach to life, understood as the art of living.